Editorial - Martha Cleveland-Innes; Sawsen Lakhal (The Canadian Network for Innovation in Education (CNIE), 2021)
More than one year after the beginning of the Covid-19 pandemic, we release a delayed Issue #3, Fall 2020, of CJLT. As an education journal, we were not immune to the effects of the pandemic. Most authors and reviewers work in some sector of education, as does the editorial team of the journal. The demand on education to continue near-normal delivery, while keeping students safe, created innovative responses alongside unskillful use of varying types of distance delivery and technology-enabled learning. The illumination of the complexity, challenges, and, for some, the benefits of such alternative education delivery methods is unprecedented. Insight, debate, and critique on the topics of remote teaching and the more sophisticated online design and delivery is more common than it was a year ago.